Linking sustainable use policies to novel economic incentives to stimulate antibiotic research and development - Ursula Theuretzbacher; Christine Årdal; Stephan Harbarth (MDPI AG, 2017)
There is now global recognition that antibiotic resistance is an emerging public health threat. Policy initiatives are underway to provide concrete suggestions for overcoming important obstacles in the fight against antibiotic resistance, like the alarming current paucity of antibacterial innovation. New economic models are needed as incentives for the discovery and development of novel antibacterial therapies especially for infections with too few patients today to justify private sector research and development (R&D) investments. These economic models should focus on rewarding the innovation, not the consumption of the antibiotic since sustainable use policies will reduce selection pressure and slow the emergence of resistance. To effectively stimulate greater innovation, the size of the reward must be commensurate with revenues from other therapeutic areas, estimated at about a billion dollar total pay-out. Otherwise R&D investment will continue to move away from antibiotics to areas where returns are more attractive. A potential sizeable public investment, if implemented, must be protected to ensure that the resulting antibiotics have a lengthy and positive impact on human health. Therefore, public investments in innovation should be bound to sustainable use policies, i.e., policies targeted at a range of actors to ensure the preservation of the novel antibiotics. These policies would be targeted not only at the innovating pharmaceutical companies in exchange for the reward payments, but also at governments in countries which receive the novel antibiotics at reasonable prices due to the reward payment. This article provides some suggestions of sustainable use policies in order to initiate the discussions. These are built on planned policies in the US, EU, WHO and have been expanded to address One Health and environmental aspects to form One World approaches. While further discussion and analyses are needed, it is likely that strong sustainable use policies will help to protect the sizeable public health investments.